El establecimiento de la Inquisición en Brasil: un proyecto frustrado - Santos Pereira, Ana Margarida (Pontificia Universidad Católica del Perú. Fondo Editorial, 2019)
The Inquisition of Lisbon extended its jurisdiction to the Portuguese territories of the Atlantic, including Brazil. Nonetheless, the religious authorities and the settlers themselves, or at least some, frequently requested the establishment of a court in Portuguese America. In this article, we will analyse the projects that were discussed in the 17th century, with a view to achieving that objective. Starting from the information contained in the inquisitorial documentation, we will try to show that Monarchy, Church and Inquisition had disparaging interests, and this was decisive so that none of the proposals under discussion came to be put into practice.

La Inquisición de Lisboa extendió su jurisdicción a los territorios portugueses del Atlántico, incluido, por supuesto, Brasil. Aun así, las autoridades religiosas y también los propios colonos, o al menos algunos, solicitaron con frecuencia el establecimiento de un tribunal en la colonia portuguesa de América. En este artículo, analizaremos los proyectos que se discutieron en el siglo XVII con miras a lograr ese objetivo. A partir de la información contenida en la documentación inquisitorial, intentaremos demostrar que la monarquía portuguesa, la Iglesia y la Inquisición tenían intereses dispares y esto fue decisivo para que ninguna de las propuestas en discusión se pusiera en práctica.
The Establishment of the Inquisition in Brazil: An Aborted Project
Keywords: Brasil; Inquisición; Proyectos; Iglesia; Política Colonial; https://purl.org/pe-repo/ocde/ford#6.01.01